2007
DOI: 10.1158/0008-5472.can-06-1650
|View full text |Cite
|
Sign up to set email alerts
|

Role for Amplification and Expression of Glypican-5 in Rhabdomyosarcoma

Abstract: Overexpression of genes, through genomic amplification and other mechanisms, can critically affect the behavior of tumor cells. Genomic amplification of the 13q31-32 region is reported in many tumors, including rhabdomyosarcomas that are primarily pediatric sarcomas resembling developing skeletal muscle. The minimum overlapping region of amplification at 13q31-32 in rhabdomyosarcomas was defined as containing two genes: Glypican-5 (GPC5) encoding a cell surface proteoglycan and C13orf25 encompassing the miR-17… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 45 publications
(52 reference statements)
7
78
0
Order By: Relevance
“…GPC6 encodes a smaller protein (∼350 aa) and contains nov-nsSNVs at positions that are highly conserved (GERP score above 5) in 2 of 16 nonhypermutated tumors as well as in 1 hypermutated tumor. GPC6 encodes a glypican, a class of cell surface coreceptors for proteases implicated in cell growth and division (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…GPC6 encodes a smaller protein (∼350 aa) and contains nov-nsSNVs at positions that are highly conserved (GERP score above 5) in 2 of 16 nonhypermutated tumors as well as in 1 hypermutated tumor. GPC6 encodes a glypican, a class of cell surface coreceptors for proteases implicated in cell growth and division (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The results of that study demonstrated a higher GPC5 expression in tumoral compared to that in normal skeletal muscle tissues; this overexpression triggered cell proliferation by modifying the cell surface distribution of FGF2, HGF and Wnt1A receptors (27). A recent publication indicated that GPC5 regulates rhabdomyosarcoma cell proliferation by activating the Hedgehog (Hh) signaling pathway.…”
Section: A B C Dmentioning
confidence: 94%
“…Similar to other glypican members, the overexpression and knockdown of GPC5 expression in rhabdomyosarcoma have been shown to cause increased and decreased cell proliferation, respectively. It was demonstrated that GPC5 increases cell proliferation through potentiating the action of FGF2, hepatocyte growth factor (HGF) and Wnt1A (27). Reduced GPC6 expression has been reported in retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Glypicans are bound to the surface of plasma membranes and play an important role in the control of cell division and growth regulation. Deregulation of proteoglycans has been reported especially in sarcomas [44]. Glypican 5 and miR-17-92 are co-expressed in cancer and expanding over the genomic region, which is amplified in many tumors [44].…”
Section: Eur J Immunol 2010 40: 888-898mentioning
confidence: 99%
“…Deregulation of proteoglycans has been reported especially in sarcomas [44]. Glypican 5 and miR-17-92 are co-expressed in cancer and expanding over the genomic region, which is amplified in many tumors [44]. However, whether these gene products are directly interacting with each other is not known.…”
Section: Eur J Immunol 2010 40: 888-898mentioning
confidence: 99%